Fatal neurocryptococcosis in a Colombian underage patient - Maria Clara Noguera; Patricia Escandón; Merle Arévalo; Jorge Piedrahita; Elizabeth Castañeda (Journal of Infection in Developing Countries)
Cryptococcosis is a life-threatening mycosis reported mainly in human adults with low frequency in children. High mortality rates may occur in cases with late diagnosis therefore, a timely suspicion of this pathology is important. Cryptococcus gattii is the less prevalent species complex predominantly isolated from apparently normal hosts. We report a fatal case of neurocryptococcosis in a Colombian minor without known risk factors, in Barranquilla, Colombia. The patient was hospitalized for neurological assessment with a recent history of intense headache, vomiting, anorexia, loss of consciousness, drowsiness, inability to recognize family members, disorientation, aphasia and anxiety. Despite initiating antifungal treatment after isolation of the fungus from cerebrospinal fluid (CSF), the patient died early due to his deteriorated condition.